State-of-the-art developments in fuels, combustors, and combustion technologies for low-emission aero gas turbine engines - Mussa Demewez Ali; Mhadi A. Ismael; Amanullah Moral; Mohammed El-Adawy; Khalid Elserfy; Medhat A. Nemitallah (Fuel, 2026)

Contamination levels, eco-health risks, and source identification of some potentially toxic elements in roadside dust along the Indus Highway (N-55), Pakistan using compositional data analysis - Amanullah; Wajid Ali; Saad Khan; Said Muhammad; Abdur Raziq; Muhamamd Nafees; Imran Ud Din (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Photocatalytic and antifouling performance of g-C3N4, CeO2, and ZnO-grafted PVDF/TiO2 nanohybrid membranes: a comparative study - S. Nivedita; M. Induja; Mani Durai; Karthikeyan Manivannan; Vinoth Kumar Raja; Nagaraj Murugan; Dharani Shanmugapriya; Vijayakumar Paranthaman; Amanullah Fatehmulla; Ramkumar Vanaraj; Paskalis Sahaya Murphin Kumar (Environmental Geochemistry and Health, 2026)

Comparative analysis of enzymatic and transcriptional regulation of sugar metabolism during muscadine and bunch grape berry development - Imrul Mosaddek Ahmed; Tushar Dhanani; Meenakshi Agarwal; Md Amanullah; Mehboob B. Sheikh (Acta Physiologiae Plantarum, 2026)

RPS20 as a colorectal cancer predisposition gene: an integrated review of the literature and evaluation in 9738 cases and 161,403 controls - Anusha Amanullah; Juan Fernández-Tajes; Guler Gul; Steve Thorn; Ignacio Soriano; Joseph C. Ward; Kitty Sherwood; Ian Tomlinson (Familial Cancer, 2026)

Two-stage deep learning model for non-destructive leaf counting in tomato crops - Amanullah Quamer; Nima Asgari; Joshua M Pearce (Computers and Electronics in Agriculture, 2026)

Soil Carbon Stock Estimation in Sugarcane Cropland Using the Cool Farm Tool - Amanullah Adeel; A. S. Jadhav (Agricultural Research, 2026)

Unveiling curzerenone chemistry, metabolism, and broad-spectrum biological effects: A comprehensive review - Hamza Elhrech; Abdelaali Balahbib; Naoufal El Hachlafi; Nasreddine El Omari; Meriem El Fessikh; Mohammed Amanullah; Learn-Han Lee; Tarik Aanniz; Gokhan Zengin; Abdelhakim Bouyahya (Food Bioscience, 2026)

Exploring soil organic carbon variability: a machine learning approach and comparison of Sentinel-2 A and Landsat 8 in google earth engine - Amanullah Adeel; Siddhi Rajendra Ingawale; A. S. Jadhav (Environmental Sustainability, 2026)

Unearthing potential of aluminum-modified biochar for saline-alkali soil rejuvenation and microbial diversity enhancement - Saba BABAR; Amanullah BALOCH; Muhammad QASIM; Jiyuan WANG; Xiangling WANG; Rashid IQBAL; Ali M. ABD-ELKADER; Khurram SHEHZAD; Xiaoyang XIA; Cuncang JIANG (Pedosphere, 2026)

Ambient synthesis of La embedded ZIF-8 core-shell adsorbent for selective fluoride removal from Tanzanian geothermal water: Performance, kinetics, and isotherms - Minjung Song; Eujung Kim; A.G. Ramu; Mani Durai; Amanullah Fatehmulla; Elangovan Erusappan; Handol Lee; Dongjin Choi (Journal of Environmental Chemical Engineering, 2026)

Chemical characterization, phytochemical profiling, antioxidant and antidiabetic properties of Halopithys incurva (Hudson) Batters, 1902: In vitro and in silico approaches - Youssra Aalilou; Güneş Ak; Bouchra Rossafi; Mustapha Hassoun; Hanaa Moussa; Gokhan Zengin; Samir Chtita; Mohammed Amanullah; Abdelhakim Bouyahya; My El Abbes Faouzi (Algal Research, 2026)

Employing Google Earth Engine and Machine Learning Algorithms for Soil Organic Carbon Mapping: A Comparison Study of Sentinel-2A and MODIS Images in Croplands - Amanullah Adeel; A. S. Jadhav (Journal of the Indian Society of Remote Sensing, 2026)

Growth, Yield, and Oil Quality of Sesame (Sesamum indicum L.) Cultivars Under Varying Row Spacings and Biofertilizer Application - Saddam Hussain; Abdul Qayyum; Amanullah Jan; Muhammad Ilyas; Izaz Ahmad; Uzair Ahmed; Emanuele Radicetti; Adil Mihoub; Aftab Jamal; Yaser Hassan Dewir (International Journal of Plant Production, 2025)

Investigation on performance enhancement of a novel solar still using metallic fins: an experimental and 5E analysis - Subramaniyan Chinnasamy; Omar Bait; B. Kalidasan; Amanullah Fatehmulla (Clean Technologies and Environmental Policy, 2025)

Green engineering of chitosan-bioactive glass for efficient removal of Cr(VI) and Cu(II) ions from aqueous systems - S. Revathi; Mohammed Amanullah; Awad Saeed Al-Samghan; J. John Joseph; P. Pazhanisamy; R. Lavanya; Thandapani Gomathi (Environmental Monitoring and Assessment, 2025)

Structure–function relationship of the brown seaweed Undaria pinnatifida laminaran: Protein kinase C-mediated mucus secretion and gut barrier restoration - Kit-Leong Cheong; Lin Chen; Si-Yuan Lu; Amanullah Sabir; Jianping Chen; Zhuo Wang; Suresh Veeraperumal; Jude Juventus Aweya; Xian-Qiang Chen; Saiyi Zhong; Karsoon Tan; A.M. Abd El-Aty (Carbohydrate Polymers, 2025)

Unraveling the synergistic effect of biochar and potassium solubilizing bacteria on potassium availability and rapeseed growth in acidic soil - Saba Babar; Amanullah Baloch; Muhammad Qasim; Jiyuan Wang; Xiangling Wang; Ali M. Abd-Elkader; Zeinab El-Desouki; Xiaoyang Xia; Cuncang Jiang (Journal of Environmental Management, 2025)

Identifying the Optimal Sugarcane Residue Percentage for Soil Enhancement: A Statistical and GIS Approach - Amanullah Adeel; A. S. Jadhav (Circular Economy and Sustainability, 2025)

Explainable and Reduced-Feature Machine learning models for shape and drag prediction of a freely moving drop in the sub-critical Weber number regime - Md Amanullah Kabir Tonmoy; Taofiqhasan Mahmood; Chadwick Sevart; Yue Ling; Yi Wang (Chemical Engineering Journal, 2024)

Bioinformatics and functional analysis of EDS1 genes in Brassica napus in response to Plasmodiophora brassicae infection - Jalal Eldeen Chol Atem; Longcai Gan; Wenlin Yu; Fan Huang; Yanyan Wang; Amanullah Baloch; Chinedu Charles Nwafor; Alpha Umaru Barrie; Peng Chen; Chunyu Zhang (Plant Science, 2024)

In-situ synthesis of V2AlC@V2O5/TiO2 immobilized over honeycomb support with vanadium oxide electron transfer mediator for stimulating selective CO2 photoreduction through bi-reforming in a monolith reactor - Muhammad Tahir; Beenish Tahir; Naveen Kumar; Mohamed Al Marzooqi; Mohammad Siraj; Amanullah Fatehmulla (Fuel, 2024)

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

Retraction Note: Mitigating the economic impact of COVID-19 on wind energy: assessing the role of green finance policies and the levelized cost of energy - Riaz Hussain Jamali; Amanullah Bughio; Raza Ali Tunio; Ghansham Das (Environmental Science and Pollution Research, 2024)

How Does Sustainable Management Practices Affect Weed Flora and Tuber Yield of Potato Crop in Mediterranean Environment? - Emanuele Radicetti; Khan Amanullah; Verdiana Petroselli; Mariam Atait; Mohamed Allam; Adil Mihoub; Aftab Jamal; Alireza Taab; Ghulam Haider; Morad Mirzaei; Roberto Mancinelli (Journal of Crop Health, 2024)
Intensive potato cultivation affects weed species composition by selecting dominant and competitive weeds that represent a constraint of potato productivity. Field experiments were conducted during 2015 and 2016 growing seasons to examine the effects of soil tillage (plowing (PL), spading (SM), sub soiling (SS)) and fertilizer source (mineral (Min) and organic (Org)) on potato yield and weed community under Mediterranean environment. A randomized complete block design with three replications was adopted. Weed density and biomass were measured at the potato harvesting time. Weed density was highest in SS, intermediate in SM, and lowest in PL (43.8, 40.3, and 28.8 plants m −2 ). Similar trend was observed in weed biomass. Weed density and biomass were higher in Org than Min (42.1 vs . 36.4 plants m −2 and 129.6 vs . 117.9 g m −2 , respectively). Perennial, monocot, and dicot weed species were the most abundant in subsoiling (13.1, 9.3 and 34.5 plants m −2 ). Density of perennial and dicot species were higher in Org than Min. Monocots were mostly linked with Min, while dicots were mainly associated with Org. Although tuber yield was higher in PL and Min (481.9 and 627.5 g m −2 of DM), it was affected by growing season and might be associated to SM and Org. Although the study shows that increased weed biodiversity in the system, achieved with more sustainable practices, proves to be an obstacle to potato production, the adoption of spading machine applied in combination with mineral and organic fertilizers could be a valid alternative to plowing. Further studies are required to develop sustainable agricultural techniques able to improve the competitive capacity of crops and reduce the selection of dominant weed species.

Exploring farmers’ coping strategies and adaptive measures against the extended drought in Balochistan, Province of Pakistan - Hashim Durrani; Ainuddin Syed; Sharon Gourdji; Ghulam Murtuza; Amanullah Mengal (Environment, Development and Sustainability, 2023)

Gaseous elemental mercury emissions from informal E-Waste recycling facilities in Pakistan - Mureed Kazim; Jabir Hussain Syed; Perihan Binnur Kurt-Karakus; Merve Ozkaleli Akcetin; Sumaira Akram; Askin Birgul; Melik Kara; Yetkin Dumanoglu; Mustafa Odabasi; Zafeer Saqib; Jawad Nasir; Amanullah Mahar; et al. (Waste Management, 2023)

Plane invariant segmentation of computed tomography images through weighted cross entropy optimized conditional GANs in compressed formats - Usman Khan; Amanullah Yasin (Medical & Biological Engineering & Computing, 2023)

Fine genetic mapping confers a major gene controlling leaf shape variation in watermelon - Ming Xu; Meiling Gao; Sikandar Amanullah; Yu Guo; Xiuping Bao; Yaru Duan; Xiujie Liu; Jixiu Liu; Yue Gao; Feishi Luan (Euphytica, 2023)

RETRACTED ARTICLE: Mitigating the economic impact of COVID-19 on wind energy: assessing the role of green finance policies and the levelized cost of energy - Riaz Hussain Jamali; Amanullah Bughio; Raza Ali Tunio; Ghansham Das (Environmental Science and Pollution Research, 2023)

Mathematical dynamics of measles transmission with real data from Pakistan - Olumuyiwa James Peter; Sania Qureshi; Mayowa M. Ojo; Ratchada Viriyapong; Amanullah Soomro (Modeling Earth Systems and Environment, 2023)

Correction to: A recessive gene Cmpmr2F confers powdery mildew resistance in melon (Cucumis melo L.) - Taifeng Zhang; Haonan Cui; Feishi Luan; Hongyu Liu; Zhuo Ding; Sikandar Amanullah; Manlin Zhang; Tingting Ma; Peng Gao (Theoretical and Applied Genetics, 2023)

A recessive gene Cmpmr2F confers powdery mildew resistance in melon (Cucumis melo L.) - Taifeng Zhang; Haonan Cui; Feishi Luan; Hongyu Liu; Zhuo Ding; Sikandar Amanullah; Manlin Zhang; Tingting Ma; Peng Gao (Theoretical and Applied Genetics, 2023)

Molecular mapping of candidate gene regulating fruit stripe trait in watermelon - Xiaoxue Liang; Meiling Gao; Sikandar Amanullah; Yu Guo; Hongguo Xu; Xiaosong Liu; Xiujie Liu; Jixiu Liu; Yue Gao; Chengzhi Yuan; Xuezheng Wang; Feishi Luan (Euphytica, 2022)

Biochar in Combination with Nitrogen Fertilizer is a Technique: To Enhance Physiological and Morphological Traits of Rice (Oryza sativa L.) by Improving Soil Physio-biochemical Properties - Izhar Ali; Quan Zhao; Ke Wu; Saif Ullah; Anas Iqbal; He Liang; Jing Zhang; Ihsan Muhammad; Amanullah; Abdullah Khan; Asad Ali Khan; Ligeng Jiang (Journal of Plant Growth Regulation, 2022)

Mapping of genetic loci controlling fruit linked morphological traits of melon using developed CAPS markers - Sikandar Amanullah; Benjamin Agyei Osae; Tiantian Yang; Farhat Abbas; Shi Liu; Hongyu Liu; Xuezheng Wang; Peng Gao; Feishi Luan (Molecular Biology Reports, 2022)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

CAPS marker-base genetic linkage mapping and QTL analysis for watermelon ovary, fruit and seed-related traits - Benjamin Agyei Osae; Sikandar Amanullah; Hongyu Liu; Shi Liu; Arvind Saroj; Chen Zhang; Tai Liu; Peng Gao; Feishi Luan (Euphytica, 2022)

Risk characteristics, government subsidies and farmers' willingness to adopt water‐saving irrigation techniques * - Lun Hu; Amanullah Channa; Xiaotong Liu; Ghulam Rasool Lakhan; Muhammad Meraj; Qian Lu; Qingjin Wang (Irrigation and Drainage, 2022)
This paper explores the mechanisms of risk preference, risk awareness and farmers' willingness to adopt water‐saving irrigation techniques in response to government subsidies. Data, collected from farmers in Gansu Province, China, were analysed using mediation and moderation effect models. The empirical evidence from this study indicates that willingness to adopt water‐saving irrigation techniques increased with an increase in government subsidies but decreased with risk awareness due to farmers' attitude of risk preferences. Secondly, the interaction between farmers' risk awareness and risk preference determines their willingness to adopt water‐saving irrigation techniques where risk awareness plays an intermediary role in both cases. Nevertheless, the cautionary role of risk awareness is more obvious, so risk‐averse farmers are significantly less willing to adopt irrigation techniques than risk preference farmers. Also, government subsidies have a significant moderating effect on farmers' risk preferences and risk awareness irrespective of their usage of farming techniques.

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

Social vulnerability to seismic-tsunami hazards in district Gwadar, Balochistan, Pakistan - Amanullah Mengal; Katsuichiro Goda; Muhammad Ashraf; Ghulam Murtaza (Natural Hazards, 2021)

Identification of putative genetic regions for watermelon rind hardness and related traits by BSA-seq and QTL mapping - Tiantian Yang; Sikandar Amanullah; Jiahui Pan; Guixiang Chen; Shi Liu; Shuangwu Ma; Jiming Wang; Peng Gao; Xuezheng Wang (Euphytica, 2021)

The influences of fly ash on stabilization for Cd in contaminated soils - Ping Wang; Ronghua Li; Di Guo; Zhanyu Guo; Amanullah Mahar; Juan Du; Zengqiang Zhang (Environmental Science and Pollution Research, 2020)

Effect of feeding different levels of discarded date palm (Phoenix dactylifera) on digestibility, milk yield, and composition in Damani sheep - Naveed Iqbal; Muhammad Tahir Khan; Haq Amanullah; Israru Din; Hamayun Khan; Muqader Shah; Muhammad Mushtaq (Tropical Animal Health and Production, 2019)

Genetic mapping reveals a candidate gene for egusi seed in watermelon - Feishi Luan; Chao Fan; Lei Sun; Haonan Cui; Sikandar Amanullah; Lili Tang; Peng Gao (Euphytica, 2019)

A bi-functional cobalt-porphyrinoid electrocatalyst: balance between overpotential and selectivity - Sk Amanullah; Abhishek Dey (JBIC Journal of Biological Inorganic Chemistry, 2019)

Lanosterol Suppresses the Aggregation and Cytotoxicity of Misfolded Proteins Linked with Neurodegenerative Diseases - Arun Upadhyay; Ayeman Amanullah; Ribhav Mishra; Amit Kumar; Amit Mishra (Molecular Neurobiology, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Petrology of calc-alkaline/adakitic basement hosting A-type Neoproterozoic granites of the Malani igneous suite in Nagar Parkar, SE Sindh, Pakistan - M. Qasim Jan; Amanullah Laghari; M. Asif Khan; M. Hassan Agheem; Tahseenullah Khan (Arabian Journal of Geosciences, 2018)

Volatile terpenoids: multiple functions, biosynthesis, modulation and manipulation by genetic engineering - Farhat Abbas; Yanguo Ke; Rangcai Yu; Yuechong Yue; Sikandar Amanullah; Muhammad Muzammil Jahangir; Yanping Fan (Planta, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Ibuprofen Induces Mitochondrial-Mediated Apoptosis Through Proteasomal Dysfunction - Arun Upadhyay; Ayeman Amanullah; Deepak Chhangani; Vibhuti Joshi; Ribhav Mishra; Amit Mishra (Molecular Neurobiology, 2016)

Mahogunin Ring Finger-1 (MGRN1), a Multifaceted Ubiquitin Ligase: Recent Unraveling of Neurobiological Mechanisms - Arun Upadhyay; Ayeman Amanullah; Deepak Chhangani; Ribhav Mishra; Amit Prasad; Amit Mishra (Molecular Neurobiology, 2016)

Impact of aortic root size on left ventricular afterload and stroke volume - Anders Sahlén; Nadira Hamid; Mohammed Rizwan Amanullah; Jiang Ming Fam; Khung Keong Yeo; Yee How Lau; Carolyn S. P. Lam; Zee Pin Ding (European Journal of Applied Physiology, 2016)

Potential role of phytohormones and plant growth-promoting rhizobacteria in abiotic stresses: consequences for changing environment - Shah Fahad; Saddam Hussain; Asghari Bano; Shah Saud; Shah Hassan; Darakh Shan; Faheem Ahmed Khan; Fahad Khan; Yutiao Chen; Chao Wu; Muhammad Adnan Tabassum; Ma Xiao Chun; et al. (Environmental Science and Pollution Research, 2015)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

Disease resistance in rice and the role of molecular breeding in protecting rice crops against diseases - Shah Fahad; Lixiao Nie; Faheem Ahmed Khan; Yutiao Chen; Saddam Hussain; Chao Wu; Dongliang Xiong; Wang Jing; Shah Saud; Farhan Anwar Khan; Yong Li; Wei Wu; et al. (Biotechnology Letters, 2014)